PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Rohmah, Nazilul; Imron, Ali (Universitas YPPI Rembang, 2023)
This study aims to determine the effect of good corporate governance, leverage, and company size on profitability. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This type of research is a type of quantitative research. The sampling technique used was a side purposive technique. The research sample consisted of 15 companies with a total of 75 data studied. The data used is secondary data obtained from the Indonesia Stock Exchange (IDX). The data analysis method used was multiple linear regression analysis using the SPSS version 23 program. The results showed that the board of independent commissioners had a significant positive effect on profitability (ROA), leverage (DER) and firm size had a significant negative effect on profitability (ROA), while institutional ownership and audit committee have no effect on profitability (ROA). Keywords : Institutional ownership, independent board of commissioners, audit committee, leverage, and company size.